Occurrence of the Retromolar Foramen in Dry Mandibles of South-Eastern Part of India: A Morphological Study with Review of the Literature. (29th September 2014) - Potu, Bhagath Kumar; Kumar, Vinod; Salem, Abdel-Halim; Abu-Hijleh, Marwan
Abstract : The retromolar foramen (RMF) is a rare anatomical structure situated in the retromolar fossa behind the third molar tooth. When it is present, the foramen is connected with the mandibular canal and is believed to transmit neurovascular structures that provide accessory source to the mandibular molars and the buccal area. Reports from the literature show that the presence of RMF could pose a challenge in complete blockage of the inferior alveolar nerve during mandibular surgeries. We report the incidence of retromolar foramen from ninety-four dry mandibles of south-eastern part of Karnataka State, India. The foramen was observed in 11 mandibles out of 94 included in the study (11.7%). In three mandibles, the foramen was present bilaterally (3.2%) and in three it was on the left side (3.2%) and in five it was on the right side (5.3%). For the first time, we also measured the dimensions of the retromolar area and distance of the foramen from third molar tooth to understand its risks during the surgical extraction of the lower third molar tooth. A thorough review of the literature has also been done to compare the present findings with the studies reported from the various populations.